A review on the properties of straw insulation for buildings. (2nd May 2022) - Zhou, Yaping; Trabelsi, Abdelkrim; El Mankibi, Mohamed
Abstract: Applying thermal insulation in building envelope is a promising approach for energy efficient building. The mainstream thermal insulation products are however produced from petrochemicals causing high energy consumption and adverse effect on environment during their production as well as arising reuse and recycle issues. Insulation materials derived from local agricultural straws have attracted increasing attention due to their superior hygrothermal performance, low life cycle cost and low carbon footprint. This paper aims to provide a comprehensive review on the two categories of straw insulation products, i.e., straw bales and straw composites. In particular, available researches on the properties including thermal insulation, moisture, mechanical, durability and fire resistance are thoroughly reviewed and discussed with the consideration of different factors. In addition, the existing literature on the life cycle assessment of straw wall by comparison with tradition wall is presented.